Orbital Pseudotumor, It is Really a Pseudotumor - Demirel, Ersan Ersin; Çavdar, Müfide; Demirel, Soner; Düz, Cem; Kütükde, Derya (Fırat University, 2012)
Orbital inflammatory pseudotumor is a nonspecific phenomenon which has unknown etiology and pathogenesis. All the orbital soft tissue compartments can be affected locally or diffusely. Clinically, a sudden-onset eye pain is one of the most common characteristics of this disease, in addition swelling and redness of the eyelids, proptosis, and limitation of eye movements can be occured. It may be associated with some diseases, such as Wegener's granulomatosis, sarcoidosis, idiopathic mediastinal fibrosis, retroperitoneal fibrosis, cholangitis, vasculitis, and lymphoma. The diagnosis usually is made clinically and radiologically supported. The case underwent a treatment in an outer center due to orbital cellulites then he was suspected malignancy in another center and biopsy was planned. After referral to our clinic he was successfully treated for pseudotu orbila.

Orbital psödotümör etiyolojisi ve patogenezi tam olarak bilinmeyen, nonspesifik inflamatuar bir olaydır. Tüm orbita içi yapılar lokal ya da diffüz olarak tutulabilir. Kliniğinde ani başlangıçlı göz ağrısı en önemli belirti olmakla beraber, göz kapaklarında ödem ve kızarıklık, göz hareketlerinde kısıtlanma ve propitozis görülebilir. Wegener granülomatozisi, sarkoidoz, idiopatik mediastinal fibrozis, retroperitoneal fibrozis, kolanjit, vaskulit ve lenfoma gibi bazı hastalıklar ile birlikte görülebilir. Tanısı çoğunlukla klinik olarak konulur ve radyolojik olarak desteklenir. Olgumuza bir dış merkezde orbital selülit nedeniyle tedavi uygulanmış, diğer bir merkezde ise malignite şüphesiyle biyopsi planlanmıştır. Kliniğimize başvurduğunda ise psödotümör orbita tanısı konulmuş ve başarıyla tedavi edilmiştir.
Psödotümör Orbita, Gerçekten Psödo Bir Tümör